Odpowiedzi

2009-12-10T22:25:52+01:00
A) x+2y=-13 /x(-1)
b) 3x+y=-5 /x(-2)
c) -x+4y=2 /x(-1/2)
d) x-1/2y= 1 /x4
e) 3x-3y=1 /x2/3
f) x+3/4y=0 /x(-8/3)
Najlepsza Odpowiedź!
2009-12-10T22:27:50+01:00
A) x+2y=-13 /*(-1)
-x-2y=13



b) 3x+y=-5 /*(-2)
-6x-2y=10


c) -x+4y=2 /:(-2)
x/2 -2y=-1

d) x-1/2y= 1 /*(4)
4x-2y=4
e) 3x-3y=1 /*(2/3)
2x-2y=2/3
f) x+3/4y=0 /*(8/3)
8/3 x+2y=0 /*(-1)
-8/3 x-2y=0
2 5 2
2009-12-10T22:28:15+01:00
A) x+2y=-13/÷(-1)

b) 3x+y=-5/÷(-2)

c) -x+4y=2/÷(-½)

d) x-1/2y= 1/×4

e) 3x-3y=1/÷⅔

f) x+3/4y=0/× (-⁸/₃)